Annual report 2002 of the CGIAR System-wide Genetic Resources Programme - CGIAR Systemwide Genetic Resources Programme (2003)
This report examines the new Treaty and its ramifications for the Future Harvest Centres (p. 5). It also covers two of the crucial elements of developing a global system, the costing studies (p. 14) that supply part of the rationale for the Global Crop Diversity Trust, and the launch of the Trust itself (p.11). There are articles too on recent developments in the System-wide Information Network for Genetic Resources (SINGER, p. 17) and on regular programme activities (p. 2). In the period covered by this report, SGRP received funding from Japan, Netherlands, Switzerland and the World Bank. The CGIAR System-wide Program on Participatory Research and Gender Analysis in Technology Development and Institutional Innovation (PRGA) hosted at CIAT provided funding for the workshop on participatory plant breeding. SGRP is grateful for all the support it receives.